Pengaruh Mediasi Positive Emotion pada Sales Promotion dan Shopping Lifestyle terhadap Impulse Buying Gen Z Pengguna Shopee di Kota Surabaya - Christina Sudyasjayanti; Vivian Lie (Universitas Tarumanagara, 2022)
The purpose of this research is to find out to determine the influence of sales promotion and shopping lifestyle on impulse buying with positive emotion as an intervening variable. This research uses a Likert scale questionnaire which is distributed to 170 Gen Z respondents who are 17 to 24 years old and Shopee users who live in Surabaya. The result of questionnaire distribution states that 140 questionnaires are feasible to be analyzed as the sample. The results of path coefficients show that the value of sales promotion and shopping lifestyle significantly affected impulse buying, and sales promotion affects positive emotion. Whereas positive emotion affects impulse buying and positive emotion does not mediate between sales promotion and impulse buying. It can be concluded that three hypotheses are accepted and two hypotheses are rejected. Penelitian ini bertujuan untuk mengetahui pengaruh sales promotion dan shopping lifestyle terhadap impulse buying dengan positive emotion sebagai variabel intervening. Penelitian ini menggunakan kuesioner skala Likert yang dibagikan kepada 170 responden Gen Z berusia 17-24 tahun, pengguna Shopee di Kota Surabaya. Hasil dari penyebaran kuesioner menyatakan bahwa sebanyak 140 kuesioner yang layak untuk dianalisis sebagai sampel. Hasil path coefficients menunjukkan bahwa nilai sales promotion dan shopping lifestyle berpengaruh terhadap impulse buying, dan sales promotion berpengaruh terhadap positive emotion. Sedangkan, positive emotion berpengaruh terhadap impulse buying dan positive emotion tidak memediasi hubungan antara sales promotion dengan impulse buying. Dapat disimpulkan bahwa 3 hipotesis diterima dan 2 hipotesis ditolak.